The Impact of Gamification on Changing Preventive Behaviors in Public Health Education - Naderizadeh, Mohammad; Mohammad Alipour, Narges; Rabiei, Mahnaz; Jalalpour , Seyedeh Sedigheh (Mental Health and Lifestyle Journal, 2026)
Traditional public health education methods face challenges such as reduced motivation and audience engagement. Gamification, as an innovative approach that utilizes game elements in non-game contexts, has high potential to improve interaction and the effectiveness of health education. This study aimed to propose and validate a gamification model for teaching and strengthening disease-preventive behaviors within the cultural context of Iran. This research employed a mixed-methods design (qualitative–quantitative) and was conducted in two stages. In the qualitative phase, data were collected through semi-structured interviews with 22 experts in health, education, and technology using a grounded theory approach. Data were analyzed through open, axial, and selective coding. In the quantitative phase, a researcher-made questionnaire was developed based on the conceptual model; its validity and reliability were confirmed. The questionnaire was distributed among the statistical sample, and data were analyzed using Structural Equation Modeling (SEM) with AMOS version 24. The qualitative analysis yielded 462 open codes, 99 concepts, and 22 categories, organized into a paradigmatic model consisting of causal conditions (motivational and social applications), contextual conditions (culture and technology), intervening conditions (constraints and accelerators), strategies (incentives and technology), and outcomes (increased awareness and behavioral change). The quantitative analysis confirmed the model fit (CMIN/DF = 2.888, CFI = 0.935, RMSEA = 0.071). The hypotheses regarding the effect of motivational applications on strategies (β = 0.893) and strategies on preventive outcomes (β = 0.897) were supported at the 95% confidence level. Gamification is an effective tool for changing preventive behaviors in health education. The proposed model provides a framework for policymakers and health professionals to enhance motivation and participation, improve community health, and reduce healthcare costs.